2002
DOI: 10.1108/07363760210420568
|View full text |Cite
|
Sign up to set email alerts
|

The seven year itch? Mall shoppers across time

Abstract: The present study investigates changes in the shopping behavior of today's mall patrons as opposed to those in the early 1990s. Data collected in the sample surveys included respondents' demographic attributes, shopping motivations, situational factors, and purchase behaviors. Although no differences were found between the demographics of the respondents in the earlier and later periods, we discovered significant differences in shopping patterns and purchase behaviors. Compared with the shoppers in the early 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 14 publications
6
65
1
1
Order By: Relevance
“…In the same line, Nicholls et al (2002) found that today's mall patrons tend to be more leisure driven than shoppers in the early 1990s. Wakefield and Baker (1998) found that the mall environment influences the desire to stay and re-patronage intentions to the mall.…”
Section: Entertainmentsupporting
confidence: 56%
“…In the same line, Nicholls et al (2002) found that today's mall patrons tend to be more leisure driven than shoppers in the early 1990s. Wakefield and Baker (1998) found that the mall environment influences the desire to stay and re-patronage intentions to the mall.…”
Section: Entertainmentsupporting
confidence: 56%
“…According to (Nicholls et al, 2002) Shopping integrate a social experience outside the house and there is a relationship between time spent and with social companions. Some customers may analysis the shopping experience as a basis of satisfaction and a chance for social relations by .…”
Section: Social Surroundingsmentioning
confidence: 99%
“…Therefore, there is a large body of literature that studied the consumer to buy. Alpha Shopping integrates a societal experience outside the house and there is a relationship between time consumed and with social companions (Nicholls et al, 2002). The surrounding material is circumstantial factor that consumers buy the effects of behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid increase in number of shopping malls and increasing demand for goods and services that are offered by these malls in Kuwait is unique in shopping mall behaviour, in an era where the consumers are making fewer mall trips (Nicholls et al, 2002;McColl-Kennedy and Kiel, 2000). The temporal shift of consumer preferences, perhaps has offered a wider selection of goods and services that will cater to the needs of the present generation consumers.…”
Section: Introductionmentioning
confidence: 99%